A comparative study of the efficacy and safety of thiocolchicoside and chlorzoxazone in patients with acute musculoskeletal pain - Rajeev Kumar Togiti; Raj Kumar Goud K; Kiran D; Ramakrishna K; Suresh Babu Sayana (Asian Journal of Medical Sciences, 2023)
Background: Thiocolchicoside and chlorzoxazone are commonly used muscle relaxants for the management of acute musculoskeletal pain. However, there is limited evidence comparing their efficacy and safety. Aims and Objectives: The aim of the study was to compare the efficacy and safety of thiocolchicoside and chlorzoxazone in patients with acute musculoskeletal pain. Materials and Methods: This was a randomized, open-label, parallel-group study conducted in a tertiary care hospital. A total of 50 patients with acute musculoskeletal pain were randomized to receive either thiocolchicoside (8 mg) or chlorzoxazone (500 mg) thrice daily for 7 days. The primary outcome measure was the change in pain intensity from baseline to Day 7, assessed using a visual analog scale (VAS). The secondary outcome measures were the percentage reduction in pain intensity and the incidence of adverse events. Results: The baseline characteristics of the patients were similar in both groups. The mean baseline pain intensity was 7.2±1.3 in the thiocolchicoside group and 7.1±1.2 in the chlorzoxazone group. After 7 days of treatment, both drugs significantly reduced pain intensity from baseline. The mean pain intensity at Day 7 was 2.9±1.1 in the thiocolchicoside group and 3.1±1.2 in the chlorzoxazone group. The percentage reduction in pain intensity was 59.7%±12.3% in the thiocolchicoside group and 56.3%±11.5% in the chlorzoxazone group. However, there was no statistically significant difference between the groups in terms of pain intensity reduction (P=0.453). Conclusion: The results of this study suggest that thiocolchicoside and chlorzoxazone are equally effective and safe in the management of acute musculoskeletal pain. The choice of drug may depend on the patient’s individual characteristics and risk factors.